Christian Faith as an Important Element of Culture and Integral Education - Giuseppe Mari (Nicolaus Copernicus University in Toruń, 2018)
The article, referring to the words of the Letter to Diognetus on Christians as the soul of the world, points to the importance of the Christian faith and its believers - Christians in Europe and in the world, especially in the field of culture and education, which are characterized by an integral approach. This problem is analysed in successive three stages: 1) first, integrity is indicated as an essential feature of the Christian faith and education that has been clearly marked from the very beginnings of Christianity; 2) shows faith as the basic expression of human identity, also consistent with the freedom that gives its identity; 3) critically analyses the secularity, indicating in this context the need to promote the integrity of the upbringing of the person and the cultural and social benefits that the Christian faith can bring. Especially during the present loss of the ability to distinguish between important and less important things, when apart from the need to rethink the idea of secularity, the possibility of a positive culmination is pointed out. Christian faith can be an important element of integral culture and integral education in action for humanization. In this action, reason and faith, as "two wings" can lead to true wisdom.